Communicating high-tech products - a comparison between print advertisements of automotive premium and standard brands. (2016) - Baccarella, Christian Vincenzo; Scheiner, Christian Willi; Trefzger, Timm Florian; Voigt, Kai-Ingo
Is there a difference in advertising high-tech products between premium and standard brands? A systematic content analysis of 492 print advertisements from the automotive industry has been conducted, focusing on brand name, logo, and slogan as well as on the amount and types of presented information cues. The findings of this study show that premium brands tend to focus more on corporate branding than standard brands, whereas standard brands place a greater emphasis on product-related branding compared to premium brands. Moreover, premium brands communicate significantly more information per ad than standard brands, and they also differ regarding the types of presented information. This study complements current theoretical and conceptual knowledge with empirical evidence. The findings are particularly valuable for practitioners as they enable marketing decision makers to better review their own advertising strategies.